Technology adoption by Czech consumers - Švábík, Prokop; Motlová, Veronika; Gašková, Jana; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
This thesis utilizes the theories and models of existing technology adoption research based on which it proposes the ARG model, a custom model for study of adoption of the researched technology (augmented reality glasses). This model is then tested by field research using a survey and statistical analysis which evaluates the validity of proposed relationships between individual variables of the model in the context of the researched topic and target group. The performance of the ARG model is then compared to the most commonly used and relevant adoption models. Last but not least, the current state of adoption of augmented reality glasses by Czech consumers is analyzed. The paper offers several conclusions and recommendations for future research of this topic as well as application of the models presented in this paper or any similar adoption models for that matter. Due to the extreme novelty of the technology, consumers lack information about the product and despite very positive attitude towards the technology are currently hesitant to adopt it. There are noticeable differences between various demographic groups, especially Gender and Age.
Vedoucí práce: Veronika Motlová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses